PERANCANGAN APLIKASI MEDIA PEMBELAJARAN DASAR DESAIN GRAFIS BERBASIS ANDROID MENGGUNAKAN WEB KODULAR - Muyasir Muyasir; Rahmat Musfikar (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Based on the initial observations made, the researchers found the problem that teachers were less than optimal at using learning media. There are several factors that often make the student's learning process limited; these factors include that each student has different abilities in absorbing material. This study aims to develop an android application that can be a learning medium for DDG (Basic Graphic Design) material based on user needs, so as to facilitate teaching and learning activities at the State Vocational High School 1 Mesjid Raya Aceh Besar. This study uses the R & D (research and development) method and the system usability scale (SUS) method in testing the feasibility of information systems. The results of the final evaluation evaluation carried out on this application from 12 respondents including 10 students and 2 teachers got a score of 80 and were included in grade B based on the percentile rank graph, and a good rating based on adjective rank, so this application was categorized as good in meeting user needs. and quite easy to use by users.